Immunological parameters of dental alloy corrosion; A study of gingival inflammation after placement of stainless steel crown - Indriyanti, Ratna (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2008)
The dental alloy is widely used in many fields of dentistry as a restoration material, orthodontic, prosthodontic, oral surgery and endodontic treatments. Naturally, most of the metallic materials without exception to stainless steel alloy will experience a process of corrosion in a form of electrochemical reaction to achieve thermodynamic equilibrium. The corrosion process in the oral cavity is due to the reaction of metal with saliva as an oral cavity electrolyte fluid. SSC has preformed restoration material conform with dental anatomy, manufactured from stainless steel alloy which is formable and adaptable to the teeth. Stainless Steel Crown generally made of austenitic stainless steel 18/8 of AISI 304 group contain chrome 18% and Nickel 8%, can be used as a restoration for teeth with excessive caries, crown fracture, email hypoplasia, or restoration after endodontic treatment. The toxic effect of Ni+2 released due to corrosion process may cause an inflammation of the gingiva and periodontal tissue. Laboratorically this condition indicated by the expression of pro-inflammation cytokines as immunological parameters such as IL-6, IL-8, TNF and IL-1Î² whose main role is to initiate and enhance any inflammation responses. The presence of pro-inflammation cytokines can be detected as soon as 1 hour after placement of SSC by examination of gingival crevicular fluid (GCF) by ELISA technique. The magnitude of the toxic effect depends on corrosion rate and ions release which is influenced by metal chemical composition, environment temperature and pH, metal wear due to abrasion and friction, soldering if any, and elongation of the metal. Conclusion: The release of Ni+2 during corrosion process after placement of SSC cause gingival inflammation which is indicated by the change of the immunological parameters.